Respostas
respondido por:
1
H² = C² + C2²
(Pitágoras, hipotenusa ao quadrado é igual ao cateto ao quadrado mais o outro cateto ao quadrado)
H² = 15,9² + 12,4²
H² = 252,81 + 153,76
H² = 406,57
H = raiz de 406,57
H = 20,16
(Pitágoras, hipotenusa ao quadrado é igual ao cateto ao quadrado mais o outro cateto ao quadrado)
H² = 15,9² + 12,4²
H² = 252,81 + 153,76
H² = 406,57
H = raiz de 406,57
H = 20,16
tatiiane1:
show
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás